2022
DOI: 10.1021/acsphotonics.2c00426
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Free-Standing Polymer Membranes Sensitized by CsPbX3 Nanocrystals as Gain Media for Low Threshold, Multicolor Light Amplification

Abstract: Lead halide perovskite nanocrystals (NCs) are highly suitable active media for solution-processed lasers in the visible spectrum, owing to the wide tunability of their emission from blue to red via facile ion-exchange reactions. Their outstanding optical gain properties and the suppressed nonradiative recombination losses stem from their defecttolerant nature. In this work, we demonstrate flexible waveguides combining the transparent, bioplastic, polymer cellulose acetate with green CsPbBr 3 or red-emitting Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…These include vertical cavity surface emitting lasers (VCSELs), ,, devices based on whispering gallery mode structures, ,, and lasers employing Fabry–Pérot resonators . An interesting recent study described in ref demonstrated ASE-active waveguides prepared as free-standing, flexible, water-resistant membranes composed of functionalized perovskite nanocrystals and a cellulose acetate polymer.…”
Section: Novel Nanocrystal-based Optical Gain Materialsmentioning
confidence: 99%
“…These include vertical cavity surface emitting lasers (VCSELs), ,, devices based on whispering gallery mode structures, ,, and lasers employing Fabry–Pérot resonators . An interesting recent study described in ref demonstrated ASE-active waveguides prepared as free-standing, flexible, water-resistant membranes composed of functionalized perovskite nanocrystals and a cellulose acetate polymer.…”
Section: Novel Nanocrystal-based Optical Gain Materialsmentioning
confidence: 99%
“…Third, QDs may suffer from spectral diffusion, which causes fluctuations in the electronic energy transitions . In this context, recent advances to improve the quality of colloidal PQDs have permitted to attain transparent films made from cubic CsPbBr 3 nanocrystals, which have been integrated into a photonic crystal resonator to observe weak light–matter coupling properties, as evidenced by the observation of amplified spontaneous emission. , In another recent achievement, it has been shown that PQD films, whose absorption spectra partially preserve the excitonic features present in the colloidal cubic CsPbBr 3 nanocrystals used as building blocks, exhibit the excitonic optical Stark effect under very intense photoexcitation . Both results imply substantial advancement in the field of perovskite photonics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,11 ] To date, several systems of fluorescent semiconductor nanomaterials and deposition techniques have been investigated as part of the efforts to demonstrate efficient and stable multicolor lasers. Among them, group III‐V quantum wells using epitaxial growth, [ 12 ] group II‐VI semiconductors using chemical vapor deposition (CVD), [ 13 ] and colloidal perovskites, [ 14 ] and organic molecules [ 15 ] using spin‐casting have been employed as the active media for the demonstration of multi‐wavelength optical gain and lasing. To achieve the lasing at two or more different wavelengths simultaneously, different types of optical cavities such as distributed‐feedback (DFB) cavity, [ 16 ] whispering‐gallery‐mode (WGM) cavity, [ 17 ] and nanowire [ 6 ] and nanosheet [ 18 ] self‐resonant cavities have been implemented.…”
Section: Introductionmentioning
confidence: 99%